2020
DOI: 10.1101/2020.07.10.197210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Male and female reproductive fitness costs of an immune response in natural populations

Abstract: Parasites can mediate host fitness both directly, via effects on survival and reproduction, or indirectly by inducing host immune defense with costly side-effects. The evolution of immune defense is determined by a complex interplay of costs and benefits of parasite infection and immune response, all of which may differ for male and female hosts in sexual lineages. Here, we examine fitness costs associated with an inducible immune defense in a fish-cestode host-parasite system. Cestode infection ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 54 publications
(54 reference statements)
0
22
1
Order By: Relevance
“…If fibrosis reduces the ability or motivation to build a nest and defend it against rivals and egg predators, we expect fibrosis rates of successfully nesting males to be lower than non-nesting males caught nearby outside of the aggregation of nests. In each of two lakes (Roselle and Boot) we confirmed that nesting males had lower fibrosis than males who had failed to nest (odds ratios of 0.41 and 0.56 respectively, both P < 0.01), controlling for infection status and body size (De Lisle and Bolnick 2020). The mechanisms of these fitness costs of fibrosis are still under investigation, but may include increased metabolic demands, locomotor constraints from more rigid tissues, or constrained female ovary expansion due to adhesion to surrounding tissue.…”
Section: Main Textmentioning
confidence: 61%
“…If fibrosis reduces the ability or motivation to build a nest and defend it against rivals and egg predators, we expect fibrosis rates of successfully nesting males to be lower than non-nesting males caught nearby outside of the aggregation of nests. In each of two lakes (Roselle and Boot) we confirmed that nesting males had lower fibrosis than males who had failed to nest (odds ratios of 0.41 and 0.56 respectively, both P < 0.01), controlling for infection status and body size (De Lisle and Bolnick 2020). The mechanisms of these fitness costs of fibrosis are still under investigation, but may include increased metabolic demands, locomotor constraints from more rigid tissues, or constrained female ovary expansion due to adhesion to surrounding tissue.…”
Section: Main Textmentioning
confidence: 61%
“…Our study was motivated by inter-population variation in threespine sticklebacks’ ability to encapsulate parasitic tapeworm S. solidus (Weber et al 2017b). The inter-population variation probably stems from an evolutionary trade-off between the benefit of resistance (early encapsulation of the worm) and the risk of organ adhesion, excessive fibroblast proliferation, and ultimately partial sterility in the stickleback (Weber et al, in preparation; De Lisle and Bolnick 2020). Previous records on peritoneal fibrosis in threespine stickleback are mostly lacking (but see Hoffman 1975, p.175), although the phenomenon is found in numerous populations across the species’ circumpolar range.…”
Section: Discussionmentioning
confidence: 99%
“…This fibrosis has been found to effectively suppress growth of certain parasites, or even lead to parasite death (Weber et al, in preparation). However, the benefits of tissue repair and parasite containment can come with a cost from chronic type 2 immune response during persistent or recurrent infections, which may develop into serious health issues or even death (Gause et al 2013; De Lisle and Bolnick 2020). Here, we measure the extent of evolutionary conservation of a key immune phenotype, fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-human species, surveying two wild populations of stickleback confirmed that the presence of fibrosis scar tissue is associated with reduced parasite burden in both male and female fish. However, fibrotic fish had lower reproductive success (reduced male nesting and female egg), indicating big costs of the lingering immunopathology (De Lisle and Bolnick 2020).…”
Section: Introductionmentioning
confidence: 99%